KAJIAN STRATEGI PENINGKATAN KUALITAS TEH HITAM ORTHODOKS DI PT. PERKEBUNAN NUSANTARA VIII (PTPN VIII Persero) UNIT KEBUN GEDEH, KABUPATEN CIANJUR - Marimin dan Eneng Karmila (Jurnal Teknologi Industri Pertanian, 2004)
ABSTRACTGlobalization era has forced company to increase its product quality so it can be the winner in competition. In tea world, problems that Indonesia has to face are decreasing of tea price, decreasing amount of tea market, and increasing amount of tea that unsold in joint market office (KPB Jakarta). Alternatives that can be used to overcome these problems are increasing tea farm work, adjust tea quality in accordance to the customer demands and controling the tea production process.STRAKTA-THO is a system to formulate strategy to increase tea quality that contains centralization process system, basic data management system (data of tea farm work, data of customer quality tea, data of production), basic model management (Balanced Scorecard model, Quality Function Deployment  model, Statistical Process Controlmodel, strategy model), and dialog model management system. STRAKTA-THO was implemented and verified using data of Gedeh tea farm from year 2000 to 2002. BSC model verification show that Gedeh tea farm performance is in good status with total score of 4,403. Customer tea quality are tea variety, tea grade, and tea watering taste. Priorities of process production are quality handling of tea, withering and spooling-milling. The best priority of  aplicated strategy in Gedeh tea farm is quality handling strategy of ISO 9001;2000.Key words : tea quality improvement strategy, Balanced Scorecard, Quality Function Deployment